Assessing the effectiveness of the UK's insolvency regulatory framework at deterring insolvency practitioners' opportunistic behaviour. Issue 2 (3rd July 2019) - Wood, John M.
ABSTRACT: This article examines whether the increase in insolvency regulation is adequate to deter insolvency practitioners from using their discretion to charge excessive fees. To understand how insolvency regulation has developed the article will commence with a review of the historical origins of insolvency work and how it became associated with opportunistic behaviour. Next, the insolvency practitioner will be examined along with the recognised professional regulators to examine how their practices have helped to shape insolvency law. IP discretion and their decision making will then be considered to demonstrate how opportunism has continued to exist in administration, before the measures that have been taken over the last twenty years to address some of these issues are explored. The Australian regulatory system will then be reviewed as a comparison to the UK, before finally recommendations are made to the effect that insolvency practitioners should be further monitored in the use of their discretion.